PEMBERDAYAAN USAHA EKONOMI PRODUKTIF (UEP) BAGI MASYARAKAT MISKIN DI KECAMATAN MIOMAFFO TIMOR KABUPATEN TIMOR TENGAH UTARA (TTU) - Ghawa Rado, Bernadus; Khristina Kiha, Emilia (Aksara Public, 2019)
The purpose of service is Institutional Capacity Development and Productive Economic Business of the Joint Business Group. The service location is in the Esa Oesena Faculty in East Miomaffo District, Timor Tengah Utara Regency. Participants who were the object of the training in this service were members of the "Flamboyant" Joint Business Group. The process of empowering the poor through the Joint Business Group in Oesena Village begins with the introduction stage, namely by forming groups. There are 3 important phases in the empowerment process, namely: Initial Phase, Participatory Phase and Emancipatory Phase. From this activity 10 selected groups who will then receive further assistance are ready to be empowered and developed according to their capabilities and capacities. Then for the development of the capacity and institutions of the Joint Business Group there are several approaches that can be carried out by empowering parties. or empowerment actors that the implementation of the process in achieving empowerment goals can be achieved through an empowerment approach which is abbreviated as 5P, namely: Possibility, Strengthening, Protection, Supporting and Maintenance. In connection with the above empowerment approach until now the method carried out by the empowering actors in this case the North Central Timor District Social Service is bribing, protection and temporary maintenance for the possibility and reinforcement fully handed over to field facilitators. Where the steps taken by the field facilitators and the Joint Business Group in Oesena Village are as follows: increasing the intensity of meetings and fostering group leadership, while in financial administration there are additional bookkeeping such as Activity Plan Books, KUBE Members Welfare Development Cards, Books Acceptance of KUBE Assistance, While this effort carried out by field facilitators is a partnership